2017
DOI: 10.3390/molecules22122059
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves the Quality of Inferior Bovine Oocytes and Promoted Their Subsequent IVF Embryo Development: Mechanisms and Results

Abstract: The inferior oocytes (IOs), which are not suitable for embryo development, occupy roughly one-third or more of the collected immature bovine oocytes. The IOs are usually discarded from the in vitro bovine embryo production process. Improving the quality of the inferior oocytes (IOs) and make them available in in vitro embryo production would have important biological, as well as commercial, value. This study was designed to investigate whether melatonin could improve the quality of IOs and make them usable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 59 publications
2
34
0
2
Order By: Relevance
“…GDF9 and BMP15 are limited to oocyte cytoplasm, and GDF9 and BMP15 addition improves expression of genes related with oocyte maturation and cumulus expansion in porcine oocytes during IVM [53]. Melatonin treatment moderates reduction of relative values of BMP15 and GDF9 mRNA caused by oocyte denudation during IVM in the bovine [6], and also upregulates expression of BMP15 and GDF9 in inferior oocytes, which are beneficial for oocyte maturation and embryo development in cattle [54]. Melatonin supplementation enhances expression of GDF9 gene via melatonin membrane receptors in oocytes, which are beneficial for bovine oocyte IVM [55].…”
Section: Discussionmentioning
confidence: 99%
“…GDF9 and BMP15 are limited to oocyte cytoplasm, and GDF9 and BMP15 addition improves expression of genes related with oocyte maturation and cumulus expansion in porcine oocytes during IVM [53]. Melatonin treatment moderates reduction of relative values of BMP15 and GDF9 mRNA caused by oocyte denudation during IVM in the bovine [6], and also upregulates expression of BMP15 and GDF9 in inferior oocytes, which are beneficial for oocyte maturation and embryo development in cattle [54]. Melatonin supplementation enhances expression of GDF9 gene via melatonin membrane receptors in oocytes, which are beneficial for bovine oocyte IVM [55].…”
Section: Discussionmentioning
confidence: 99%
“…While some reports have examined these intracellular processes of melatonin in oocytes [62][63][64][65], the details remain unclear. It has been reported that melatonin controls the expression of genes related to oocyte maturation including mitochondrial function [53,60,66,67], antioxidative enzymes [53,59,67,68], apoptosis [52,[65][66][67][68][69], cumulus cell expansion [51,61,70], and oocyte maturation factors [61,67]. Furthermore, epigenetic mechanisms such as DNA methylation and histone acetylation have also been reported [59,66,71].…”
Section: Oocyte Maturation Embryo Development and Melatoninmentioning
confidence: 99%
“…Under the situations in which the cells require ATP for their biological activities including in embryo development (143)(144)(145), or under the situation of ATP production deficiency caused by mitochondrial dysfunctions or other insults, melatonin always promotes ATP production. For example, melatonin improves aging-related ATP deficiency in cybrids (96), restores the normal ATP production in a parkinsonian phenotype zebra fish which express high oxidative stress (88) and increases ATP levels in neural stem cells (NSCs) which require high energy to differentiate into oligodendrocytes and neurons (146).…”
Section: 3melatonin On Atp Production In Mitochondriamentioning
confidence: 99%